Banana genome to enrich fruit basket - Uma, S.; Backiyarani, S.; Saraswathi, M. S.; Mustaffa, M. M. (Indian Horticulture, 2019)
The decoding of banana genome will provide a platform for understanding existing genetic diversity, associating gene(s) with phenotypes and exploiting natural genetic diversity in developing superior genotypes either through MAS or genetic engineering. Banana genome information will not only benefit the banana but also other crops which are having similar unique characters like polyploidy, parthenocarpy etc. Hence Musa genome can be considered as a model non-grassy monocots and could be used to study a number of aspects like the functional genetics of polyploidy, gene silencing and tissue or developmental specific expression of duplicate genes, alternate fitness of diploid and tetraploid cytotypes in different habitats. The M. balbisiana, an important ancestor of cultivated banana, is likely to be sequenced by India in the near future. Once the major genomes are decoded. Sequencing data and their analysis will be made much more simpler adding volumes of musa genome sequence data that will provide adequate information on the genes related to yield, quality, pest and disease resistance etc. which could be exploited in improvement of banana and plantain and other crops as well.